Emotion regulation: an exploration of gender differences among adolescents in Malaysia - Siti Rashidah Yusoff,; Suzana Mohd Hoesni,; Noor Azimah Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The intricate dynamics of gender roles significantly shape emotion regulation (ER) among adolescents, underscoring the importance of understanding these assigned roles in comprehending adolescents' emotional experiences. This study aimed to investigate and analyze in detail the central aspects of disparities between genders in the utilization of ER strategies. The formulation of the hypotheses aimed to predict significant distinctions between boys and girls, particularly in cognitive reappraisal (CR) and expressive suppression (ES) strategies. A cross-sectional design was employed and implemented in 27 public secondary schools across 12 states in Malaysia. A total of 1,718 adolescents, both boys and girls who did not have any current or prior clinical issues became participants in this study. Using the Malay version of the Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA), the study's findings contradicted the proposed hypotheses. The findings showed no gender disparities in CR and ES. These findings provide valuable insights for parents, caregivers, teachers, and adolescents, offering a nuanced understanding of ER during the critical stages of adolescence. The implications of ER across genders may guide the development of targeted interventions to address potential gender disparities and mitigate the risk of psychopathological issues.